Metode Kisah dalam Meningkatkan Motivasi Belajar dan Kemampuan Bercerita pada Pembelajaran Sejarah Kebudayaan Islam di Madrasah Ibtidaiyah - Azizeh , Siti Nur (LPPPM STAI Darul Hikmah Bangkalan, 2021)
Learning Islamic Cultural History is a learning that tends to be monotonous so that students easily feel bored. The reason is because in delivering the material generally by the lecture method without any learning media used. This makes student interest and motivation decrease, as a result the material described by the teacher cannot be accepted and understood easily. It has an impact on the low ability to tell stories to students. Therefore, teachers are required to provide innovation in creating fun learning, one of which is by changing the method in delivering the subject matter. The application of the story method is considered appropriate and relevant to Islamic Cultural History lessons, thereby increasing learning motivation and storytelling skills. The story method can create an attractive learning atmosphere, so students will feel the joy of learning. That way, students will have a desire or desire in the form of a desire to know which is accompanied by power or effort to achieve the goals they want to achieve, this is called the emergence of motivation learning In addition, the story method using pictures can strengthen students 'memory of historical stories, which can provide a real picture of these historical stories so that in this case it can improve students' ability to tell stories. The stages in the application of the story method that educators need to pay attention to include, among others, planning, presentation of material, correlation, conclusion and evaluation. Regarding the design, it can be adjusted to the needs and learning objectives.